Geopolitics Tension, Wars and Its Impact on Energy/Oil Crisis: Russia – Ukraine War Case Study - Arinaldo Adma; Margaretha Hanita (Pusat Publikasi Nusantara, 2025)
The intensifying geopolitical competition amid the current multipolar global order has elevated the risk of interstate armed conflicts, exemplified by the Russia-Ukraine war in 2022. This conflict has triggered significant food and energy inflation worldwide, resulting in approximately 70 million people losing access to electricity. Understanding the interplay between geopolitical events and the energy crisis is essential for nations to develop effective anticipation, coping, and adaptation strategies aimed at preserving national energy security, particularly concerning petroleum commodities. This study explores critical energy security strategies focusing on supply-side measures such as energy diversification, energy transition, diversification of import sources, and the enhancement of strategic reserves. Additionally, the research examines the role of targeted subsidies as a fiscal tool to stabilize consumer purchasing power and maintain demand within the constraints of national fiscal capacity. Employing a qualitative approach through literature review and policy analysis, this study synthesizes existing frameworks and practices to propose comprehensive strategies for energy resilience in the face of geopolitical risks. The findings highlight the necessity of a multifaceted approach that integrates supply diversification with fiscal policies to ensure energy security. The implications underscore the importance for policymakers to strengthen energy systems' adaptability and fiscal mechanisms to mitigate the impacts of global geopolitical disruptions.